Common Carotid Intima-Media Thickness Relates to Cardiovascular Events in Adults Aged <45 Years. Issue 4 (April 2015) - Eikendal, Anouk L.M.; Groenewegen, Karlijn A.; Anderson, Todd J.; Britton, Annie R.; Engström, Gunnar; Evans, Greg W.; de Graaf, Jacqueline; Grobbee, Diederick E.; Hedblad, Bo; Holewijn, Suzanne; Ikeda, Ai; Kitagawa, Kazuo; et al.
Abstract : Although atherosclerosis starts in early life, evidence on risk factors and atherosclerosis in individuals aged <45 years is scarce. Therefore, we studied the relationship between risk factors, common carotid intima-media thickness (CIMT), and first-time cardiovascular events in adults aged <45 years. Our study population consisted of 3067 adults aged <45 years free from symptomatic cardiovascular disease at baseline, derived from 6 cohorts that are part of the USE-IMT initiative, an individual participant data meta-analysis of general-population–based cohort studies evaluating CIMT measurements. Information on risk factors, CIMT measurements, and follow-up of the combined end point (first-time myocardial infarction or stroke) was obtained. We assessed the relationship between risk factors and CIMT and the relationship between CIMT and first-time myocardial infarction or stroke using a multivariable linear mixed-effects model and a Cox proportional-hazards model, respectively. During a follow-up of 16.3 years, 55 first-time myocardial infarctions or strokes occurred. Median CIMT was 0.63 mm. Of the risk factors under study, age, sex, diastolic blood pressure, body mass index, total cholesterol, and high-density lipoprotein cholesterol related to CIMT. Furthermore, CIMT related to first-time myocardial infarction or stroke with a hazard ratio of 1.40 per SD increase in CIMT, independent of risk factors (95% confidence interval, 1.11–1.76). CIMT may be a valuable marker for cardiovascular risk in adults aged <45 years who are not yet eligible for standard cardiovascular risk screening. This is especially relevant in those with an increased, unfavorable risk factor burden. Abstract : Supplemental Digital Content is available in the text.